A new design of UHF tag antenna for clothing identification using SRR - Badr Nasiri; Ahmed Kh. Errkik; Jamal Zbitou (Universitas Ahmad Dahlan, 2021)
In this paper, we present a new antenna for radio frequency identification (RFID) tag operating in the Moroccan ultra high frequency (UHF) band around 868 MHz, this antenna is designed on a flexible plastic substrate of relative permittivity 3 and low tangential losses which is 0.002. The proposed tag is designed to identify clothing in supermarkets. The tag antenna has a miniature size of 38 mm in length and 26 mm in width. This miniature size was obtained by using two rectangular split ring resonator (RSRR). The impedance matching of the RFID chip with the antenna was carried out by a double T-matching structure. The antenna is designed, simulated and optimized using computer simulation technology (CST) microwave studio software and good results have been obtained in terms of impedance matching, gain and read range.